2011
DOI: 10.1590/s1678-77572011000600013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated immersion solution cycles on the color stability of denture tooth acrylic resins

Abstract: ObjectiveChemical solutions have been widely used for disinfection of dentures, but their effect on color stability of denture tooth acrylic resins after repeated procedures is still unclear. The aim of this in vitro study was to evaluate whether repeated cycles of chemical disinfectants affected the color stability of two denture tooth acrylic resins. Material and MethodsSixty disc-shaped specimens (40 mm x 3 mm) were fabricated from two different brands (Artiplus and Trilux) of denture tooth acrylic resin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 20 publications
3
39
2
9
Order By: Relevance
“…In a 2006 study of, Ertas evaluated distilled water as causing the least discoloration, with cola, tea, and coffee respectively higher, also in line with the current study (16). In 2011, Silva et al found that denture teeth could be discolored after immersion cycling in distilled water, which may be due to the internal composition of the resin constructor of artificial teeth, the water sorption phenomenon, and micro cracks caused by this sorption (17). Discoloration of denture teeth depends on the hydrophilic nature of choromogenous solutions as well as their material properties (18).…”
Section: Discussionsupporting
confidence: 80%
“…In a 2006 study of, Ertas evaluated distilled water as causing the least discoloration, with cola, tea, and coffee respectively higher, also in line with the current study (16). In 2011, Silva et al found that denture teeth could be discolored after immersion cycling in distilled water, which may be due to the internal composition of the resin constructor of artificial teeth, the water sorption phenomenon, and micro cracks caused by this sorption (17). Discoloration of denture teeth depends on the hydrophilic nature of choromogenous solutions as well as their material properties (18).…”
Section: Discussionsupporting
confidence: 80%
“…Disinfection with chemical solutions is especially mandatory for geriatric or handicapped denture wearers with compromised manual dexterity (16,17). In fact, it has been recommended as an essential procedure for prevention of cross-contamination and maintenance of a healthy oral mucosa (18).…”
Section: Introductionmentioning
confidence: 99%
“…28 Ölçü materyallerinin kimyasal dezenfeksiyonunda spreyleme yöntemi ve solüsyonda bekletme/ daldır-ma yöntemi olmak üzere iki yöntem kullanılır. 29 Irreversible hidrokolloid ölçü materyalinde dezenfektan solüsyonda bekletildiğinde hacimsel değiĢiklik meydana gelmektedir, bu yüzden daha çok spreyleme yöntemi tercih edilmektedir. 30,31 Elastomerik ölçü materyallerinin farklı solüsyonlarda daldırma yöntemi ile dezenfekte edilmesinin minimum hacimsel değiĢikliğe sebep olduğu bildirilmiĢtir.…”
Section: (Tablo 1)unclassified
“…29 Akrilik esaslı sert bir kaide astar materyali olan Tokuyama Rebase Fast II, sodyum perborat solüsyonu (Corega Tablet) ve klorheksidinle 6 ay boyunca dezenfekte edilmiĢ, renk değiĢimleri ölçül-müĢtür. Kontrol grubu dahil tüm gruplarda dikkate değer renk değiĢimi görülmüĢtür.…”
unclassified